1991
DOI: 10.1128/iai.59.5.1599-1604.1991
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of intracellular free calcium levels in HEp-2 cells infected with enteropathogenic Escherichia coli

Abstract: Enteropathogenic Escherichia coli (EPEC) are a class of diarrheagenic organisms that induce a characteristic attaching and effacing lesion in enterocytes and various cultured cell lines. Infection of cultured HEp-2 cells by EPEC isolates 2036-80 (serotype 0119) and E2348-69 (serotype 0127) resulted in significant elevation of intracellular free calcium levels, determined quantitatively with the fluorescent calcium indicator dye 2-{[2-bis (carboxymethyl)amino-5-methylphenoxyjmethyl}-6-methoxy-8-bis(carboxymethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(71 citation statements)
references
References 39 publications
6
64
0
1
Order By: Relevance
“…Thus, both the thapsigargin findings along with the BAP-TA and EDTA results indicate that the release of Ca2+ from the intracellular store is an important step in the invasion process. Similar conclusions were reached by Baldwin et al [7], who found that dantrolene, an inhibitor of Ca2+ release from the intracellular store, inhibited EPEC invasion of epithelial cells. Hence, it would appear that Ca2+ release from the intracellular store is important in the invasion process of both EPEC and P. gingivalis.…”
Section: Invasionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, both the thapsigargin findings along with the BAP-TA and EDTA results indicate that the release of Ca2+ from the intracellular store is an important step in the invasion process. Similar conclusions were reached by Baldwin et al [7], who found that dantrolene, an inhibitor of Ca2+ release from the intracellular store, inhibited EPEC invasion of epithelial cells. Hence, it would appear that Ca2+ release from the intracellular store is important in the invasion process of both EPEC and P. gingivalis.…”
Section: Invasionsupporting
confidence: 87%
“…[Ca2+] changes in Henle-407 cells utilized a 3 h incubation on ice [6], and measurements of EPEC infection of HEp-2 cells occurred over l-6 h [7,14]. Hence, the overall frequency of P. gingivalisinduced [Ca2+] flux may actually be higher than we observed in 1 h.…”
Section: (Cd+] Changesmentioning
confidence: 63%
See 1 more Smart Citation
“…EPEC signal transduction involves activation of host-cell tyrosine kinase activity leading to tyrosine phosphorylation of a 9OkDa host membrane protein, Hp90, and fluxes of intracellular inositol phosphate (IP3) and calcium (Baldwin etal., 1991;Foubister etal., 1994b;Dytoc et a/., 1994;Rosenshine et a/., 1992). Following these events, EPEC adheres intimately to the surface of the epithelial cell, accompanied by damage to host-cell microvilli and accumulation of cytoskeletal proteins beneath the adherent organism (Knutton etal., 1989;1987;Baldwin et a/., 1991;Finlay et al, 1992). A 35kb locus in EPEC, designated the LEE (!ocus of enterocyte effacement), encodes all of the known factors required for attaching and effacing lesion formation (McDaniel et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This phosphorylation leads to alterations in cell shape and in actin organisation (Knutton et al, 1989). EPEC infection also leads to raised intracellular calcium concentrations, and it seems likely that the formation of the characteristic lesion is due to calcium activation of the actin depolymerizing protein villin, leading to accumulation of actinomyosin within the lesion (Baldwin et al, 1991). At present it is unclear whether raised intracellular calcium concentrations also lead to phosphorylation of other cell membrane proteins involved in electrolyte transport across the brush border membrane.…”
Section: Enteropathogenic Escherichiu Coli (Epec)mentioning
confidence: 99%